Molecular characterization and susceptibility screening for methicillin-resistant Staphylococcus aureus reveals the dominant clones in a tertiary care hospital in Al Qassim, Saudi Arabia - Said, Kamaleldin B; Aljarbou, Ahmed N.; Alorainy, Mohamed S.; Saeed, Elhassan M. A.; Hassan, Khalid M. (International Journal of Health Sciences, 2019)
Objective: Staphylococcus aureus has become an important pathogen in hospitals worldwide. Despite its differentiation into human and animal lineages, common methods are used for genotyping. While these methods are useful, they are based on the stable genome, and hence, are insensitive to host-specific subtyping. The objectives of this study were to investigate the repeat-domain of the Clumping-Factor A gene (clfA-R) as an objective and adaptation-sensitive approach. Methodology: We have used 113 isolates for susceptibility testing and genotyping by polymerase chain reaction amplification of the clfA-R regions. Of these, 105 were from King Fahad Specialist Hospital, Buraidah and eight were published sequences used as references. Isolates were further confirmed as S. aureus by the commercial Kits. Amplicon sizes were measured and the number of the 18-bp-repeating-units in each isolate was determined against that of methicillin-resistant S. aureus COL (MRSA) sequence. Results: Results showed that all 42 nasal screening isolates (100%) and all but six isolates from clinical specimens were MRSA with 37% of the former and 50% of the latter isolates showing community-acquired-MRSA susceptibility patterns. clfA-R analysis grouped 113 isolates into 14 repeat-genotypes. The two dominant types, D and X, represented the long- and short clfA-R types found in humans and animals, respectively. Linezolid, rifampicin, and vancomycin were the drugs of choice. Conclusions: clfA-R was useful in rapid genotyping and implied host-specific phenotypic properties of the ClfA. It has been recommended that the approach used in regional laboratories for uniform strain-profiling. Future work will show more insights into the gene content and origins of clones.